Hippocampal functional connectivity across age in an App knock-in mouse model of Alzheimer's disease - Morrissey, Zachery D.; Gao, Jin; Zhan, Liang; Li, Weiguo; Fortel, Igor; Saido, Takaomi; Saito, Takashi; Bakker, Arnold; Mackin, Scott; Ajilore, Olusola; Lazarov, Orly; Leow, Alex D. (Frontiers in Aging Neuroscience, 2023)
Introduction Alzheimer's disease (AD) is a progressive neurodegenerative disease. The early processes of AD, however, are not fully understood and likely begin years before symptoms manifest. Importantly, disruption of the default mode network, including the hippocampus, has been implicated in AD. Methods To examine the role of functional network connectivity changes in the early stages of AD, we performed resting-state functional magnetic resonance imaging (rs-fMRI) using a mouse model harboring three familial AD mutations (AppNL-G-F/NL-G-F knock-in, APPKI) in female mice in early, middle, and late age groups. The interhemispheric and intrahemispheric functional connectivity (FC) of the hippocampus was modeled across age. Results We observed higher interhemispheric functional connectivity (FC) in the hippocampus across age. This was reduced, however, in APPKI mice in later age. Further, we observed loss of hemispheric asymmetry in FC in APPKI mice. Discussion Together, this suggests that there are early changes in hippocampal FC prior to heavy onset of amyloid β plaques, and which may be clinically relevant as an early biomarker of AD.